Trends in Green Banking as Productive Financing in Realizing Sustainable Development - Salsabila, Amalia; Fasa, Muhammad Iqbal; Suharto, Suharto; Fachri, Adib (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2022)
Abstract: Along with the strengthening of global attention to environmental issues, banks are transforming their behavior. Through the concept of Green Banking, banks are required to ensure that their operational activities are able to minimize the impact on the environment. This research is motivated by the operational practice of sharia banking in terms of financing distribution, where banks must begin to pay attention to the environmental impact of their operational activities. This research aim to identify the role of green banking as productive financing in realizing sustainable development. The research method used is a qualitative descriptive approach using library research. Based on the research that has been done, it can be seen that the implementation of green banking activities in sharia banking operations is still less than optimal, where the attention of the government and the policies that regulate the implementation of green banking are needed in order to optimize the contribution of banks to environmental protection and management efforts. The government also needs to continue to push for green growth as the main driver of city change from economic policies to people's lifestyles. With the achievement of optimal implementation of the green economy, it will have the potential to create new economic growth, create new jobs, and reduce poverty. Abstrak: Seiring dengan menguatnya perhatian dunia terhadap persoalan lingkungan, perbankan melakukan transformasi dalam perilaku kegiatannya. Melalui konsep Green Banking perbankan dituntut agar operasional kegiatannya mampu meminimalisir dampak yang ditimbulkan terhadap lingkungan. Penelitian ini dilatarbelakangi oleh praktik operasional perbankan syariah dalam hal penyaluran pembiayaan, dimana bank harus mulai memperhatikan dampak lingkungan dari kegiatan operasionalnya. Penelitian ini dilakukan dengan tujuan untuk mengidentifikasi peranan green banking sebagai productive financing dalam mewujudkan pembangunan yang berkelanjutan. Metode penelitian yang digunakan adalah metode pendekatan deskriptif kualitatif dengan menggunakan penelitian kepustakaan (library research). Berdasarkan penelitian yang telah dilakukan, dapat diketahui bahwa penerapan kegiatan green banking pada operasional perbankan syariah masih kurang optimal, dimana perhatian pemerintah dan kebijakan yang mengatur tentang penerapan green banking sangat diperlukan guna mengoptimalkan kontribusi perbankan terhadap upaya perlindungan dan pengelolaan lingkungan hidup. Pemerintah juga perlu terus mendorong untuk menjadikan pertumbuhan hijau sebagai penggerak utama perubahan kota dari kebijakan-kebijakan perekonomian menjadi gaya hidup masyarakat. Dengan tercapinya penerapan ekonomi hijau yang optimal maka akan berpotensi menciptakan pertumbuhan ekonomi baru, menciptakan lapangan kerja baru, serta mengurangi kemiskinan.